Occupational Therapists' Perceptions of Environmental Influences on Practice at an Inpatient Stroke Rehabilitation Program: A Pilot Study. (1st September 2015) - Skubik-Peplaski, Camille; Howell, Dana M.; Hunter, Elizabeth G.; Harrison, Anne
ABSTRACT Aims: To better understand occupational therapists' clinical decision making processes as they selected which rehabilitation environment to work in, and how the therapists perceived the environment impacted their choice of intervention. Methods: Focus group and individual interviews were conducted following observation of three occupational therapists providing interventions for 16 months with 12 clients following a stroke at an inpatient rehabilitation hospital stroke unit. Therapists could chose from three different environments for interventions: a therapy gym, homelike space, or a combination space. Results: Three themes emerged that revealed therapists' habits influenced their clinical reasoning; the environment influenced therapists' intervention choices; and therapists felt safer treating in the gym environment. Conclusion: The environment influenced the therapists' intervention choices as well as their clinical reasoning. Rehabilitation services on an inpatient stroke program may be improved if therapists increase their awareness of the influence of the environment on interventions.